Study on the Settlement Mechanism with Effect of Backfilling Method of an Underground Mine - Dequan Xuan; Zhiming Liu; Gang Huang; Jianhua Zhang; Tingting Jiang; Bo Ke (Geofluids, 2021)
The study on the subsidence of backfill mining block has been a concern of many scholars. A mechanical model of plate subsidence is established by studying the roof of a filling mining area in Luo Iron Mine in this paper. The boundary conditions are given, and the Navier method is used to solve the problem. Based on the thin plate model, the subsidence distribution map of the roof of the underground plate area is obtained. Based on the basic calculation parameters, the influence of a different foundation coefficient, mining depth, length-width ratio of plate area, elastic modulus of roof rock, and thickness of roof on the subsidence of roof is studied. According to the deflection calculation formula obtained, the expression of the internal force and stress is deduced, and the distribution of stress and shear stress on the upper and lower surfaces of the roof is analyzed. The dangerous area of the roof can be obtained, which provides a theoretical basis for the daily maintenance of mine safety.